The Impact of Coronavirus Disease 2019 Lockdown on Athletes’ Subjective Vitality: The Protective Role of Resilience and Autonomous Goal Motives - Martínez-González, Natalia; Atienza, Francisco L.; Tomás, Inés; Duda, Joan L.; Balaguer, Isabel (Frontiers in Psychology, 2021)
The lockdown resulting from COVID-19 has had a huge impact on peoples’ health. In sport specifically, athletes have had to deal with frustration of their objectives and changes in their usual training routines. The challenging and disruptive situation could hold implications for their well-being. This study examined the effect of the COVID-19 lockdown on changes in athletes’ reported eudaimonic well-being (subjective vitality) and goal motives (autonomous and controlled) over time (i.e., pre - and during-lockdown). The relationship of resilience to changes in subjective vitality was also determined, and changes in athletes’ goal motives were examined as potential mediators. Participants were 127 Spanish university athletes aged between 18 to 34 years old (M = 21.14; SD = 2.77). Approximately 4 months before the start of the lockdown in Spain (T1), athletes responded to a questionnaire assessing their resilience, goal motives and subjective vitality. Around 6 months later into the lockdown period (T2), athletes’ goal motives and subjective vitality were assessed again. Growth Modeling using hierarchical linear models revealed a significant decrease of autonomous goal motives and subjective vitality during the lockdown, but athletes did not show change over time in controlled goal motives. Path analysis, adjusting T2 measures for their corresponding T1 measures, showed that resilience significantly predicted changes in athletes’ autonomous goal motives, which then accounted for changes in subjective vitality. The indirect effect was significant. Resilience did not predict changes in athletes’ controlled goal motives. However, changes in controlled goal motives negatively predicted changes in subjective vitality during lockdown. The findings suggest negative impacts of the COVID-19 lockdown on athletes’ goals motives and eudaimonic well-being. Results also support the hypothesised mediational role of autonomous goal motives in the relationship between resilience and subjective vitality during the lockdown. As such, findings confirm the relevance of resilience to a key feature of athletes’ eudaimonic well-being and the importance of enhancing their autonomous goal striving.